2020
DOI: 10.1136/gutjnl-2019-319970
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic targeting and resistance to PARP inhibition in DNA damage repair-deficient pancreatic cancer

Abstract: ObjectiveATM serine/threonine kinase (ATM) is the most frequently mutated DNA damage response gene, involved in homologous recombination (HR), in pancreatic ductal adenocarcinoma (PDAC).DesignCombinational synergy screening was performed to endeavour a genotype-tailored targeted therapy.ResultsSynergy was found on inhibition of PARP, ATR and DNA-PKcs (PAD) leading to synthetic lethality in ATM-deficient murine and human PDAC. Mechanistically, PAD-induced PARP trapping, replication fork stalling and mitosis def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 60 publications
2
57
0
Order By: Relevance
“…Indeed, others and we found ATR (HR repair) and DNA-PKcs (non-homologous end joining, NHEJ) as corroborating pathways to ATM-signaling in PDAC [13,20,21]. In a recently published study, we showed that PARP, ATR, and DNA-PK inhibitors (PAD) act synergistically on ATM-deficient cells, leading to a lethal accumulation of DNA damage and, thus, demonstrating PAD treatment is a valuable approach that can be exploited to target ATM-mutant human PDACs effectively [13]. Consequently, we tested a putative synthetically lethal therapeutic option by multi-DDR interference (mDDRi) with PAD in a maintenance therapy setting after platinum-based induction therapy in analogy to the POLO trial for efficacy in ATM-deficient PDAC.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Indeed, others and we found ATR (HR repair) and DNA-PKcs (non-homologous end joining, NHEJ) as corroborating pathways to ATM-signaling in PDAC [13,20,21]. In a recently published study, we showed that PARP, ATR, and DNA-PK inhibitors (PAD) act synergistically on ATM-deficient cells, leading to a lethal accumulation of DNA damage and, thus, demonstrating PAD treatment is a valuable approach that can be exploited to target ATM-mutant human PDACs effectively [13]. Consequently, we tested a putative synthetically lethal therapeutic option by multi-DDR interference (mDDRi) with PAD in a maintenance therapy setting after platinum-based induction therapy in analogy to the POLO trial for efficacy in ATM-deficient PDAC.…”
Section: Introductionsupporting
confidence: 67%
“…Thus, concepts that target compensatory, mainly HR-related pathways against PARP inhibition in an ATM-deficient PDAC appear reasonable [19]. Indeed, others and we found ATR (HR repair) and DNA-PKcs (non-homologous end joining, NHEJ) as corroborating pathways to ATM-signaling in PDAC [13,20,21]. In a recently published study, we showed that PARP, ATR, and DNA-PK inhibitors (PAD) act synergistically on ATM-deficient cells, leading to a lethal accumulation of DNA damage and, thus, demonstrating PAD treatment is a valuable approach that can be exploited to target ATM-mutant human PDACs effectively [13].…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations